Room-temperature fabrication of au- and ag-incorporated carbon nanofibers by ion irradiation and their field emission properties - Yaakob, Y. (2013)
We have demonstrated the growth of Au- and Ag-incorporated carbon nanofibers (CNFs) at room temperature by Ar+ bombardment on graphite surfaces with simultaneous Au and Ag supply. The evolution of their morphology and its effects on field emission properties were investigated. The structure and density of the grown CNFs depended on the metal supply rate. The ion-irradiated surfaces with excess metal supply featured sparsely distributed conical protrusions and a wall-like structure, while the surfaces irradiated with appropriate metal supply produced densely distributed CNF-tipped cones and a needlelike structure. Compared with Ag supply, Au supply yielded fewer CNFs in terms of number density. Thus, the CNF number density was controllable by adjusting the metal supply rate and metal species. A lower threshold field and a higher emission current density were achieved in the field emission of both metal-incorporated CNFs than of pristine CNFs (without metal incorporation). Thus, it is believed that metal-incorporated CNFs are promising for practical field emission device applications.